“Evaluación de enfermedades y morfología de 8 variedades de caña de azúcar (saccharum officinarum) en soca en el huallaga central-San Martín” - Mendoza Pinchi, Homero (2006)
The objective of this investigation work was to make an evaluation about diseases and morphology of eight sugarcane varieties, in the first soca ( stem of sugarcane which reproduce after the first crop), under the agro climatic conditions in the Huallaga Central Valley. The work was made around the next places called Puerto Rico (Sector), Caspizapa (District), and Picota (province), with an average Temperature of 27.27° C for month, Relative Humidity of 80.09 % andan Accumulated Precipitation of 967.60mm, while was developed the study, a soil characterized for clay, with pH of 8, 13. Located in a tropical dry forest zone. The statistics design used was for random sampling of blocks with eight treatments and three repetitions. Finally, we found that M74-458 and M69-420 varieties have a high susceptibility to a disease root rot, which is caused for Pythium sp an Nigrospora sp (57.52 and 60.93 % of infested plants), also feeble where there wasn't identified the agent which causes the pathology (39.87 and 13.64 of infested plants) moderately susceptible. The variety P12- 7 45 (Azul Casa Grande) and (Habanesa) they both had a disease called coal of sugarcane with 1.20 and 0.42 % respectively, then we can see that Azul Casa Grande variety has a low level resistant while Habanesa variety shown a high percentage of affected plants with red rot disease which is caused by Fusarium sp. in a percentage of 13, 34, also CP7 4-205 variety with a high percentage for a big affection on the leaves in the sugarcane production area of 43.85 % caused far Periconia sacchari. And Drechslera stenopila; they all have influence in yield potential, brix, juice volume and benefits-costs relation in the first soca. According to the last results we got from statistics analysis that P12-745 variety (Azul Casa Grande) it had a high yield with 122. 72 tons cane/ha. Producing a juice volume of 60.40 m3/ha. ; brix of 20.83 % and a benefits- costs of 1. 7 4, eleven months later in the first soca. So we can say this variety has a high yield potential in the first soca than such a cane/plant g,at in ten months. The other varieties such as RB72-454, Habanesa, and M64-148 with yield of 103.17, 79.17, 98.56 tons I ha.; juice volume of 53.69, 44.37, 41.57 m3/ha. ; brix of 19.33, 18.67, 19.00 % anda benefits - costs relation of 1.46, 1.13, 1.40 respectively, we must considerate like promissory 'cause they can show different results in other agro climatic conditions.